Professional Discretion and the Law: Impact of Actuaries on the Underfunding and Decline of Private Sector Single Employer Defined Benefit Pensions in Canada. How Many "Post Nortel Pension Fiascos are Brewing in Canada? - Walker, Paul Charles (2016)
Considering that private sector single employer defined benefit pension plans must be fully funded by law, the legal issue emanating from their systemic underfunding is whether or not actuaries have been using their discretion in a manner which is within a reasonable interpretation of the margin of manoeuvre contemplated by the legislature, in accordance with the principles of the rule of law. This thesis discusses the merits of potential legal remedies to arrest the underfunding and decline in the number of private sector single employer defined benefit pensions in Canada, including the introduction of single employer target benefit plans, increasing employers access to surplus, making actuaries fiduciaries, legislating external oversight, abolishing employer-actuary agency, and mandating specific discount rates. It concludes that the best legal remedy is the establishment of an independent external actuarial oversight board